Ability and willingness to pay for health care and contribute to National Healthcare Financing Scheme among farmers in Selangor - Aizuddin AN,; Hod R,; Rizal AM,; Yon R,; Al Junid SM, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2011)
Introduction : In view of high healthcare expenditure, Malaysia also faces problems in healthcare financing. The policy option is to establish a national health financing scheme. However, it is a problem to develop mechanisms to cover social insurance package to more than one third of the population working in informal sector such as farmers. Therefore, there is an urgent need to assess the ability and willingness of the farming community. The main objective was to study the ability and willingness in the farming community to contribute to national healthcare financing scheme. Methodology : This a cross sectional study involved 400 farmers in Selangor. A total of 92.3% farmers were able to pay for the healthcare. Results : Willingness to contribute to The national healthcare financing scheme were RM2.00 per month. Conclusion : The education level influenced the ability to pay while the educational level and per capita income influenced willingness to pay.